PENENTUAN KADAR UNSUR BESI, KROMIUM, DAN ALUMINIUM DALAM AIR BAKU DAN PADA PENGOLAHAN AIR BERSIH DI TANJUNG GADING DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Mara Fajar (USU, 2013)
Abstract Have been measurement of consentration iron (Fe), aluminum (Al) and chromium (Cr) in raw water and potable water with Atomic Absorption Spectrophotometric method. Raw water samples taken from siparepare river water and potabel water taken from the water treatment tanjung gading. Into a sample of water was added HNO3(concentrated). Then determined the concentration of iron (Fe) Aluminium (Al) and chromium (Cr) using Atomic Absorption Spectrophotometer with a calibration curve. In the measurement of Fe metal in the potable water an average of 0.00 ppm while the average measurement of Fe in the raw water is 3.49 ppm. And the measurement of Al metal in the potable water an average of 0.01196 ppm while the average measurements of Al in the raw water is 0.01411 ppm. And the measurement of Cr metal in the potable water an average of 0.00118 ppm while the average measurements of Cr in the raw water is 0.00138 ppm. The results showed that the concentration of metallic iron (Fe) Aluminium (Al) and chromium (Cr) is corresponding with PERMENKES No.492/MENKES/PER/IV/2010 and PERMENKES RI Nomor : 416/MENKES/PER/IX/1990 on Drinking Water Quality Requirements and PP No.82 tahun 2001 on raw water. Keyword : Iron, Chromium and Aluminium with Atomic Absorption Spectrophotometry method